Edukasi Keamanan Pangan dan Tanaman Herbal Pada MI Avia Scientific - Manninda, Reise; Andayani, Nurita; Desmiaty, Yesi; Heryani, Aulia; Fatmawati, Yuli; Margono, Adi Dwi; Yolanda; Puspita, Rita; Endeline, Hanna Arystha; Jemmima, Jeanice; Viyoli, Divo; Ramadhani, Sasti Fauziyah (Abdi Implementasi Pancasila:Jurnal Pengabdian kepada Masyarakat, 2025)
The food safety of schoolchildren's snacks is the most important thing in improving the quality and nutrition of snacks consumed to enhance the quality of student's health. Despite ongoing efforts, many snacks still contain biological, chemical, and physical hazards, posing long-term health risks. This community service initiative focuses on using medicinal plants like tomatoes and oranges. These plants can be transformed into healthy, attractive snack alternatives such as foods and drinks rich in vitamins E, C and antioxidants. The project aims to educate students about snack food additives and the benefits of medicinal plants. Outreach activities include video presentations on snack safety and the detection of hazards. The results showed that their knowledge before the educational intervention was 72,16% and it increased to 75,69% after the intervention, resulting in a 3,53% improvement. The result of the food samples tested, which were brought by the students, also showed negative results, indicating no harmful substances were present. This counseling activity went well and increased students' awareness and understanding of the importance of choosing safe snacks. It is hoped that this activity will positively impact students' daily consumption and help them choose food more wisely.